2016
DOI: 10.18632/oncotarget.13899
|View full text |Cite
|
Sign up to set email alerts
|

Induction chemotherapy followed by concurrent chemoradiation and nimotuzumab for locoregionally advanced nasopharyngeal carcinoma: preliminary results from a phase II clinical trial

Abstract: Overexpression of epidermal growth factor receptor can be found in more than 80% of patients with locoregionally advanced nasopharyngeal carcinoma and is associated with shorter survival. In this work, we evaluated the feasibility of adding nimotuzumab to chemoradiation in locoregionally advanced nasopharyngeal carcinoma. Twenty-three patients with clinically staged T3-4 or any node-positive disease were enrolled. They were scheduled to receive one cycle of induction chemotherapy followed by intensity-modulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 27 publications
2
17
0
Order By: Relevance
“…A recent retrospective analysis by Liu and colleagues 21 also concluded NTZ could be safely combined with CCRT for treatment of LA-NPC. However, Huang et al 12 reported 34.8% of patients receiving CCRT plus NTZ experienced grade 3 to 4 mucositis. These inconsistencies could be due to obvious differences between chemotherapy regimens, where only patients receiving concurrent chemotherapy consisting of cisplatin (100 mg/ m 2 ) every three weeks or cisplatin (40 mg/m 2 ) weekly were eligible for the current study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A recent retrospective analysis by Liu and colleagues 21 also concluded NTZ could be safely combined with CCRT for treatment of LA-NPC. However, Huang et al 12 reported 34.8% of patients receiving CCRT plus NTZ experienced grade 3 to 4 mucositis. These inconsistencies could be due to obvious differences between chemotherapy regimens, where only patients receiving concurrent chemotherapy consisting of cisplatin (100 mg/ m 2 ) every three weeks or cisplatin (40 mg/m 2 ) weekly were eligible for the current study.…”
Section: Discussionmentioning
confidence: 99%
“…These inconsistencies could be due to obvious differences between chemotherapy regimens, where only patients receiving concurrent chemotherapy consisting of cisplatin (100 mg/ m 2 ) every three weeks or cisplatin (40 mg/m 2 ) weekly were eligible for the current study. However, the study by Huang et al 12 included patients who received more intensive concurrent chemotherapy regimens (75 mg/m 2 docetaxel and 80 mg/m 2 nedaplatin), which may have increased the incidence of mucositis during radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…6,7 EGFR is also highly expressed in NPC 8 and numerous studies have evaluated the efficacy of anti-EGFR targeted therapy. [9][10][11][12][13][14][15] Cetuximab (CTX) or nimotuzumab (NTZ) (anti-EGFR monoclonal antibodies) concurrent with RT could achieve comparable outcomes compared with standard cisplatin-RT. 12,14 When combined with CCRT, different results were produced.…”
mentioning
confidence: 99%